DETERMINAN PROFITABILITAS BANK MELALUI Z-SCORE, STRUKTUR MODAL, SIZE, RISIKO KREDIT DAN PERMODALAN PADA INDUSTRI PERBANKAN NASIONAL - Ananda, Anton Ferry (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2016)
This study aimed to analyze the influence of the value of the Z-Score, capital structure, size, credit risk and capital as measured by CAR on bank profitability. The object of this study is on the national banking industry. The sampling technique used in this research is purposive sampling. The sample in this study is a bank which went public on the Stock Exchange prior to the year 2013 and to publish financial statements in 2013 and 2014. The samples were 27 banks. Period study in 2013 and 2014. The analysis technique used multiple linear regression. The results showed that simultaneous Z-Score, capital structure, size, credit risk and capital effect on profitability. Partially value of the Z-Score, size, risk and CAR effect on profitability, while the capital structure policy has no effect on profitability.